Hannibal. Season three [videorecording (DVD)] - Mikkelsen, Mads, 1965-; Fishburne, Laurence, III, 1961-; Dhavernas, Caroline; Harris, Thomas, 1940- (Lionsgate, 2014)
Hannibal is on the run in Europe, accompanied by his psychiatrist, Bedelia Du Maurier, sporting a new identity, but servicing the same insatiable appetite. As the lives of Will and Jack converge toward Hannibal again, each with their own motivations to catch him once and for all, their deadly dance turns in startling and unexpected ways.